The macro- and microcirculation of the kidney. Issue 3 (September 2017) - Guerci, Philippe; Ergin, Bulent; Ince, Can
Abstract : Acute kidney injury (AKI) remains one of the main causes of morbidity and mortality in the intensive care medicine today. Its pathophysiology and progress to chronic kidney disease is still under investigation. In addition, the lack of techniques to adequately monitor renal function and microcirculation at the bedside makes its therapeutic resolution challenging. In this article, we review current concepts related to renal hemodynamics compromise as being the event underlying AKI. In doing so, we discuss the physiology of the renal circulation and the effects of alterations in systemic hemodynamics that lead to renal injury specifically in the context of reperfusion injury and sepsis. The ultimate key culprit of AKI leading to failure is the dysfunction of the renal microcirculation. The cellular and subcellular components of the renal microcirculation are discussed and how their injury contributes to AKI is described.